2018
DOI: 10.2478/rjr-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary outcomes in transcutaneous neuromuscular electrical stimulation use in patients with dysphagia

Abstract: Dysphagia is a common disorder associated with a large number of etiologies like aging, stroke, traumatic brain injury, head and neck cancer, neurodegenerative disorders, structural changes or congenital abnormalities. The type of the treatment and its results depend on the type, severity and the cause of dysphagia. The primary goal of dysphagia treatment is to improve the swallowing process and decrease the risk of aspiration. Along with the existing rehabilitation swallowing treatments, new adjunctive therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Most of the analysed investigations applied NMES with short impulses (700 µs) [ 28 , 29 , 30 , 31 , 32 , 33 , 35 , 40 , 41 ]. However, some studies used longer impulses (between 300 [ 27 ] and 800 ms [ 44 ]), which also obtained benefits; this could be due to the daily application of the treatment or to what has been suggested by Sarafoleanu [ 59 ], who stated that, with low-intensity and long impulses, it is possible to increase the recruitment of the motor units.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the analysed investigations applied NMES with short impulses (700 µs) [ 28 , 29 , 30 , 31 , 32 , 33 , 35 , 40 , 41 ]. However, some studies used longer impulses (between 300 [ 27 ] and 800 ms [ 44 ]), which also obtained benefits; this could be due to the daily application of the treatment or to what has been suggested by Sarafoleanu [ 59 ], who stated that, with low-intensity and long impulses, it is possible to increase the recruitment of the motor units.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to take into account that this is a controversial aspect of the application of NMES, since its administration, combined with simultaneous voluntary contraction, has been previously tested by Vanderthommen and Duchateau [ 53 ], who concluded that these two methods should not be used together due to the high metabolic demand caused by such a combination and to the possible fatigue that it could cause in the muscle fibres. On the other hand, Sarafoleanu and Enache [ 59 ] concluded that the combination of these two treatments induced greater muscular adaptations. The results obtained in this review are in line with the conclusions of the latter authors.…”
Section: Discussionmentioning
confidence: 99%